Reliability and sensitivity of the Notio Konect to quantify coefficient of drag area in elite track cyclists - Kordi, M.; Galis, G.; van Erp, T.; Terra, W. (European Journal of Sport Science, 2022)
Elite level cycling events are performed at speeds in excess of 50 km/h. At these speeds, over 90% of the resistance forces come from aerodynamic resistance (CDA). Recently bicycle-mounted pitot tubes, such as the Notio Konect (NK) have become more commercially available making CDA easier to measure. Its reliability and sensitivity would be useful for riders and coaches to be able to understand what constitutes as a change in CDA. Accordingly, the aim of this study was to establish the intra- and inter-effort reliability and sensitivity of the CDA measures of the NK. Seven elite level track riders were used in this study which was broken into two parts: 1) Reliability and 2) Sensitivity. For both parts of the experiment, riders performed identical efforts, riding at ~50 km/h for six laps of a 250m indoor velodrome. For reliability, the riders performed six efforts without any changes in position or resistance. For sensitivity, they performed the efforts with a rod with discs of a known diameters attached at each end to vary the CDA by a known amount. For the reliability assessment, low coefficient of variation of intra- (0.2%) and inter-effort (0.9%) reliability were measured. With regards to sensitivity, the smallest changes in resistance (from 5 - 6cm i.e., 1.2% or 0.002m2) was identified by the NK. The data in this experiment suggests that the NK is a highly reliable in measuring CDA can detect changes up to at least 1.2% in an indoor velodrome using elite level track riders.